The Effect of Linarin on Relevant Inflammatory Markers in Ovalbumin-Induced Asthma Rat Models - Kaihui Shen; Xiaohan Mei; Yawang Shao; Wenjing Zhang (Dose-Response)
Objective In the current work, we investigated and assessed the ability of the bioactive flavone linarin (LIN) to prevent asthma in the ovalbumin (OVA)-induced rat model. Methods The experimental rats’ body weight and relative lung weight were measured after each treatment. Indices of oxidative stress in lung tissue and erythrocytes were assessed. Analyses were conducted on hematological assays, measurement of histamine release in BALF fluid, and inflammatory markers found in blood and BALF, including IL-4, IL-13, TNF-α, IFN-γ, and IgE levels. For histological examination, tissue samples were collected. Results Administration of LIN significantly increased the rats’ body weight; however, their relative lung weight decreased. According to our findings, LIN significantly raised SOD, GSH, and CAT levels while suppressing MDA content. The administration of LIN resulted in a considerable reduction in IgE levels, cytokines, and hematological assay influx in the corresponding samples. Histological assessment showed that LIN treatment significantly maintained the anatomy of the lungs and decreased the infiltration of inflammatory cells. Conclusion The regulation of oxidative stress and the avoidance of pulmonary airway inflammation are two proposed methods by which LIN may reduce asthma symptoms.